Amblyomma loculosum Neumann 1907 - Velde; Nancy Vander Velde And Brian Vander; O., P. (Zenodo, 2013)
Amblyomma loculosum Neumann, 1907 The southern ocean bird tick, Amblyomma loculosum , was not reported by Kohls (1957). It has a wide distribution in the Indian Ocean and was collected on the red-footed booby ( Sula sula ), sooty tern ( Sterna fuscata ) and humans on Helen’s Reef of Palau. In other parts of its range, this tick has been found on many seabird species which are also known throughout Micronesia (Hoogstraal et al. 1976). Published as part of Velde, Nancy Vander Velde And Brian Vander & O., P., 2013, Known and potential ticks and tick-borne pathogens of Micronesia, pp. 1-26 in Micronesica 2013 (1) on page 4, DOI: 10.5281/zenodo.12117350